2004
DOI: 10.1299/jsmea.47.410
|View full text |Cite
|
Sign up to set email alerts
|

Micro-Macro Combined Simulation of the Damage Progress in Low-Alloy Steel Welds Subject to Type IV Creep Failure

Abstract: A simulation method for microscopic creep damage at grain boundaries in the fine-grain heat-affected zone of low-alloy steel welds involving high energy piping was proposed on the basis of the combination of elastic-creep FEM analysis and random fracture resistance modeling of the materials. First, the initiation and growth-driving forces of small defects were concretely determined based on microscopic observation of the damage progress at the grain boundaries of the material, taking into account dependence on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 14 publications
0
7
0
1
Order By: Relevance
“…Type IV creep damage in the FGHAZ (fine-grained heat affected zone) consists of creep cavities found in the subsurface of the piping. The mechanism of damage development is considered as follows from the perspective of continuum mechanics (Kawashima et al, 2004, Igari et al, 2011. The creep strain rate of the FGHAZ is faster than that of either the neighboring weld metal or base metal, and this can cause a tri-axial constraint in the FGHAZ depending on the difference in the creep strain rate.…”
Section: Introductionmentioning
confidence: 99%
“…Type IV creep damage in the FGHAZ (fine-grained heat affected zone) consists of creep cavities found in the subsurface of the piping. The mechanism of damage development is considered as follows from the perspective of continuum mechanics (Kawashima et al, 2004, Igari et al, 2011. The creep strain rate of the FGHAZ is faster than that of either the neighboring weld metal or base metal, and this can cause a tri-axial constraint in the FGHAZ depending on the difference in the creep strain rate.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Kawashima et al [20] reported that for 2.25%Cr1%Mo steel the creep ruptures lifetime depends on the cavity nucleation rate and cavity growth size. Creep damage accumulates due to the initiation and growth of extensive cavitation at the prior austenite grain boundaries [20]. Cavity formation predominates during the initial transient and individual cavities appear to nucleate on grain boundary carbides [20].…”
Section: The Cavity Nucleation and Growth Behavior Under High Stress mentioning
confidence: 99%
“…The results of parameter identification for FGHAZ are summarized as follows: the distribution of the grain boundary length [L] was determined as the normal distribution with a mean value of 10.5 mm and a standard deviation of 5 mm on the basis of the microscopic observation of the FGHAZ; the distribution of the initial value of fracture resistance [R 0 ] with a mean value of 0.5 and a standard deviation of 0.1607 was determined as shown in Figure 3(a) on the basis of the time history of the number density of small defects at a specific location of FGHAZ in the creep test of a welded joint; the stress dependence of F shown in Figure 3(b) was determined through a combination of the distribution [R 0 ] and the microscopic observation of a point with a prescribed stress; the parameter K is given in the literature [2,17].…”
Section: Determination Of Parameters For Simulationmentioning
confidence: 99%
“…(1) Creep damage simulation [2,12] of 40 mm-thick welded joint subject to tensile stress of 39.2 MPa at 898 K.…”
Section: Damage Simulation For Welded Joints Of P-22mentioning
confidence: 99%
See 1 more Smart Citation